Visionary women : three medieval mystics - Ruether, Rosemary Radford (1517 Media, 2023)
The influential feminist theologian Rosemary Ruether glimpses into the souls of three medieval mystics: Hildegard of Bingen, Mechthild of Magdeburg, and Julian of Norwich. Ruether's sympathetic overview evokes the new religious horizons they envisioned for Christianity.